The First Sentimental Education - Flaubert, Gustave (University of California Press, 2021)
The protagonist, Frederic Moreau, and his beloved, Mme Arnoux, are based on Flaubert's youthful infatuation with an older married woman. Frederic's puppy love for Mme Arnoux is at first steadfast and idealistic, and she remains faithful to her rather frivolous husband. Frederic's love ends in disillusionment, as do the subsequent passions of his life. His youthful ambitions lead to failure and boredom, and his idealistic views of social progress are disappoint.